Commodification of Religious Symbols In Advertising “Luwak Kopi Hitam Feat Ustadz Taufiqurrahman” (Semiotic Analysis of Roland Barthes) - Lailatul Husni; Ahmad Zulfikar Ali (Advances in Humanities and Contemporary Studies, 2021)
Various strategies are used by the media to attract public attention, one of which is the use of Islamic religious symbols. that is not surprising. Given that Indonesia is a country with the largest Muslim population in the world. The use of these symbols is nothing but used as an exchange value, to attract consumers' attention. One of the media content that uses Islamic religious symbols is the Luwak Kopi Hitam ad. For this reason, this research will examine the use of religious symbols and figures in these advertisements. With the aim of knowing the use of religious symbols and figures in the Black Coffee Luwak advertising product. This research will use qualitative research, with the semiotic approach of Roland Barthes. The results of this study indicate that religious symbols in the form of chaplain Taufiqurrahman, halal symbols, and other attributes have undergone commodification as commodities to be traded. The development of using mass media has caused religious figures and symbols to be enjoyed so widely by the public. Where a chaplain who is highly regarded and influential for the Muslim community, can convince the public's trust to consume drinks that are labeled halal. This commodification appears as an effort to influence society by creating an Islamic image and impression so that it can bring people into a consumptive culture.